Miria Contreras Bell (La Payita): Desafíos epistemológicos para una biografía - Élodie Lebeau (Les Cahiers de Framespa)
By bringing into dialogue questions specific to the Global Microhistory and History of Emotions, this article seeks to lay the theoretical foundations for a “biography in context” of Miria Contreras Bell (1928-2002), personal secretary and close friend of Chilean President Salvador Allende (1970-1973). The analysis of the sources used, mainly interviews, press releases, and correspondence, complemented by testimonies taken from biographical and autobiographical studies of other actors, seeks to understand two fundamental and dialectically linked commitments in her life: art and politics. The temporal limits of this work do not cover the entire existence of Miria Contreras, stretching from the 1960s to her death in 2002, but are rather inscribed in the chronologies of the Cold War (1947-1991), while at the same time exceeding them, in order to understand the ideological and memorial conflicts existing around our biographed figure.